Analisis Penggunaan Media Pembelajaran Digital dalam Meningkatkan Pemahaman Konsep Siswa pada Pembelajaran Kimia - Marbun, Kamucia Rojum Legi; Siregar, Mayesta; Boangmanalu, Merlin Margaretha; Simamora, Lourdes; Silaban, Ruth Grace Pinondang; Saragih, Jon Riahman (PendIPA Journal of Science Education, 2025)
This study aimed to analyze the effect of using digital chemistry learning media on students' concept understanding in chemistry learning. The method used is a literature review with a qualitative descriptive approach. Data were obtained from five scientific articles published between 2019 and 2025, focusing on the use of digital media such as learning videos, interactive multimedia, augmented reality, and online evaluation platforms. The results of the study show that the use of digital media can improve students' concept understanding of chemical materials, especially on abstract concepts. Learning videos and interactive multimedia help visualize concepts, increase learning motivation, and support information retention. The use of augmented reality also provides a more interactive and contextual learning experience, and supports the improvement of students' digital literacy. The conclusion of this study states that digital learning media has great potential in creating more meaningful and in-depth chemistry learning, but it needs to be balanced with infrastructure readiness and teacher competency development in integrating technology effectively.